2022
DOI: 10.1039/d2ta03669j
|View full text |Cite
|
Sign up to set email alerts
|

New insights into degradation of Fe–N–C catalyst layers: ionomer decomposition

Abstract: Fe-N-C catalyst can be used as a substitute for the expensive and scarce platinum-based catalysts in proton exchange membrane fuel cells (PEMFCs). However, the durability of MEA worsens as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…For example, ROS scavengers could be dispersed and/or integrated in the ionomeric phase of the cathode layer rather than in the Metal-N-C materials themselves, akin to proven stabilization approaches of proton-conducting membranes. The development of novel ionomers or inorganic proton conductors with anionic groups having a higher p K a than sulfonic acid groups may also help mitigating the formation of the most aggressive ROS (OH radicals) during the ORR . This is suggested by the strong pH dependency of ROS species formation and activity decay experienced by Fe-N-C when exposed to H 2 O 2 in different pH environments .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, ROS scavengers could be dispersed and/or integrated in the ionomeric phase of the cathode layer rather than in the Metal-N-C materials themselves, akin to proven stabilization approaches of proton-conducting membranes. The development of novel ionomers or inorganic proton conductors with anionic groups having a higher p K a than sulfonic acid groups may also help mitigating the formation of the most aggressive ROS (OH radicals) during the ORR . This is suggested by the strong pH dependency of ROS species formation and activity decay experienced by Fe-N-C when exposed to H 2 O 2 in different pH environments .…”
Section: Discussionmentioning
confidence: 99%
“…The reprotonation of the Nafion ionomer after the durability test of Fe-N-C layers was tried by Zhou et al but did not lead to any partial reactivation of the PEMFC performance, whereby it was concluded that the reason for the decreased proton conductivity through the cathode layer was due to the chemical degradation of the cathode Nafion ionomer by ROS species, as supported by 19 F nuclear magnetic resonance. 293 Interestingly, the use of a chemically more robust inorganic solid-state proton conductor, namely, cesium phosphotungstic acid, mitigated the performance loss. 293 The study and quantification of changes of ion exchange capacity, proton conductivity, and electronic conductivity throughout PGM-free cathode layers before and after durability tests certainly deserves more attention in the future.…”
Section: Mitigation Of Degradation Phenomena With Engineering Approac...mentioning
confidence: 99%
See 1 more Smart Citation
“…9–13 Particularly, Fe–N–C single atom site (SAS) catalysts are promising candidates for commercial catalysis due to their unique electronic structure and local coordination environment, which facilitate charge transfer. 14–18…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Particularly, Fe-N-C single atom site (SAS) catalysts are promising candidates for commercial catalysis due to their unique electronic structure and local coordination environment, which facilitate charge transfer. [14][15][16][17][18] The effect of different N-types on ORR activity is currently ambiguous. N-doping in carbon nanostructures has been reported to provide electrocatalytic active sites, thereby promoting ORR activities.…”
Section: Introductionmentioning
confidence: 99%